Literasi Digital pada Generasi Digital Natives - Arief Ardiansyah; Yulianti (UNISBA Press, 2022)
Abstract. Digital technology is indeed close and makes it easier for humans. In the reality of people's lives, the negative effects are more pronounced than the positive effects. We find tangible evidence such as bullying in the comments column on social media, attacking each other between groups or individuals, even many who have been entangled in legal cases due to expressing opinions and ending up reporting. This can be avoided if we have digital literacy skills. West Java Province is an area with the largest internet users and the largest contribution to internet penetration in Indonesia. However, the level of digital literacy is still in the medium category. Currently, the West Java Provincial Government and West Bandung Regency Government are still struggling with the literacy program and have not followed up on the digital literacy program. This study aims to determine the level of digital literacy which is then expected to be taken into consideration by various parties to conduct counseling in various forms. As a generation that has been close to technology since birth, the digital native generation will be the generation that will play a very important role in the progress of a region. This research is expected to describe the digital literacy ability of digital natives generation using quantitative descriptive methods in terms of 10 digital literacy competency indices from Japelidi namely, access, selection, understanding, analysis, verification, evaluation, distribution, production, participation and collaboration. The results of the data will describe the level of digital literacy competence of the digital natives generation in West Bandung Regency. Abstrak. Teknologi digital saat ini memang dekat dan mempermudah manusia. Namun efek negatif lebih banyak terasa dibanding efek positif, seperti halnya kita sering temukan perundungan di kolom komentar sosial media, saling serang antar kelompok atau individu, bahkan banyak yang terjerat kasus hukum akibat menyampaikan opini dan berujung pelaporan. Hal tersebut dapat dihindari jika kita memiliki kemampuan literasi digital. Provinsi Jawa Barat merupakan wilayah dengan pengguna internet dan kontribusi penetrasi internet paling besar di Indonesia. Namun tingkat literasi digital masih berada di kategori sedang. Saat ini Pemprov Jabar dan Pemkab Bandung Barat masih berkutat pada program literasi baca tulis dan belum ditindaklanjuti ke program literasi digital. Penelitian ini bertujuan untuk mengetahui tingkat literasi digital untuk kemudian diharapkan bisa dijadikan pertimbangan oleh berbagai pihak untuk mengadakan penyuluhan dalam berbagai macam bentuk. Sebagai generasi yang sejak lahir dekat dengan teknologi, generasi digital natives menjadi generasi yang akan sangat berperan dalam kemajuan suatu wilayah. Penelitian ini diharapkan dapat menggambarkan literasi digital generasi digital natives dengan menggunakan metode deskriptif kuantitatif ditinjau dari 10 indeks kompetensi literasi digital dari Japelidi yakni, akses, seleksi, pemahaman, analisis, verifikasi, evaluasi, distribusi, produksi, partisipasi dan kolaborasi. Hasil data akan menggambarkan tingkat kompetensi literasi digital generasi digital natives di Kabupaten Bandung Barat.